The Role of English in Merchant Marine: The Main Course or Supplemantary Course? - Rahmat, Subhan; Putri, Syafiqah; Mutmainnah, Nafsul (Journal of English Language Teaching, Literature and Culture, 2025)
This study explores the perceived role of English in maritime education at the Merchant Marine Polytechnic of Barombong, specifically questioning whether Maritime English is treated as a core or supplementary subject. Employing a quantitative approach, data were collected through a structured questionnaire administered to 100 cadets. The findings reveal a strong consensus among cadets regarding the importance of English in enhancing communication skills, building professional confidence, and supporting future career opportunities in the global maritime industry. Despite this, Maritime English remains marginalized within the curriculum, often taught separately from technical subjects and allocated minimal instructional time. The study identifies a significant gap between cadets’ linguistic needs and the current pedagogical approach. The results also align with similar local research in Indonesia, indicating a national trend of underemphasizing Maritime English in seafaring education. This research concludes with a recommendation to reposition Maritime English as a main course integrated into practical and technical maritime training to better prepare cadets for international standards and global work environments.